Enzyme Supplementation of Corn-Soybean Meal Diets Improves Performance in Broiler Chicken - Abudabos, A. (International Journal of Poultry Science, 2010)
This study was performed to evaluate the effect of feeding Bergazyme P, a commercial enzyme supplement that contain ß-pentosanase, α-amylase, glucanases and galactomannases, in standard corn-soy rations for broiler chicken from 1-49 days of age. A total of 800 one day old Cobb 500 chicks were obtained from a commercial hatchery and randomly distributed in a randomized complete block design among 12 floor pens with 4 replicate pens/treatment. Birds were divided into 3 groups: T1 = Control corn-soy diet; T2 = T1 + 250 g Bergazyme P/t or T3 = T1 + 500 g Bergazyme P/t. Significant treatment effects were determined using ANOVA. Enzyme supplementation significantly increased body weight at 42 and 49 d of age and significantly increased the breast yield at 49 d of age, suggesting that the improvement of body weight by Bergazyme is involved in the increase of the muscle weight. In both the T2 and T3 group, serum total protein concentration was significantly increased at 21 and 49 d of age. Ileal protein digestibility was significantly higher in the T2 compared to the control group. However, there is no significant difference in ileal protein digestibility between the T3 group and the control group. These findings suggest that the addition of Bergazyme P to the diets at the rate recommended by the manufacture (250g/t) uplifted productive performance mainly attributable to a higher degree of protein digestion.